Resynchronization and Defibrillation for Heart Failure : a Practical Approach. - Hayes, David L. (John Wiley & Sons, 2007)
Resynchronization and Defibrillation for Heart Failure: A Practical Approach is one of the first texts to provide caregivers with information about the background and application of this new and rapidly expanding discipline. Its four authors are cardiologists who have expertise in device management, electrophysiology, and heart failure management. The text integrates the approach and management experience of the authors three institutions. The aim is to bring together information from subspecialists in device management, electrophysiology, and heart failure management in an effort to facilita.